Wireless sensor networks an information processing approach - Zhao, Feng, 1962- (Morgan Kaufmann, 2004)
Designing, implementing, and operating a wireless sensor network involves a wide range of disciplines and many application-specific constraints. To make sense of and take advantage of these systems, a holistic approach is needed?and this is precisely what Wireless Sensor Networks delivers.Inside, two eminent researchers review the diverse technologies and techniques that interact in today?s wireless sensor networks. At every step, they are guided by the high-level information-processing tasks that determine how these networks are architected and administered. Zhao and Guibas begin with the can.
Keywords: Sensor networks.; Wireless LANs.; elektronické knihy; electronic books